Mating Induces Early Transcriptional Response in the Rat Endosalpinx: The Role of Tnf and Ra - Orihuela-Diaz, P (BioScientifica Ltd., 2021)
During mating, males provide not only the spermatozoa to fertilize the oocyte but also other stimuli that are essential for initiating and maintaining the reproductive programme in females. In the mammalian oviduct, mating regulates sperm storage, egg transport, fertilization, early embryonic development, and oestradiol metabolism. However, the main molecules underlying these processes are poorly understood. Using microarray analyses, we identified 58 genes that were either induced or repressed by mating in the endosalpinx at 3 h post-stimulus. RT-qPCR confirmed that mating downregulated the expression of the Oas1h and Prim1 genes and upregulated the expression of the Ceacam1, Chad, Chst10, Slc5a3 and Slc26a4 genes. The functional category cell-to-cell signalling and interaction was over-represented in this gene list. Network modelling identified TNF and all-trans retinoic acid (RA) as upstream regulators of the mating-induced transcriptional response, which was confirmed by intraoviductal injection of TNF or RA in unmated rats. It partially mimicked the transcriptional effect of mating in the rat endosalpinx. Furthermore, mating decreased RA levels in oviductal fluid, and RA-receptor-gamma (RARG) exhibited a nuclear location in oviductal epithelium in both unmated and mated rats, indicating RA-RARG transcriptional activity. In conclusion, the early transcriptional response regulated by mating in the rat endosalpinx is mediated by TNF and RA. These signalling molecules regulate a cohort of genes involved in cell-to-cell signalling and interactions and merit further studies to understand the specific processes activated in the endosalpinx to sustain the events that occur in the mammalian oviduct early after mating. © 2021 Society for Reproduction and Fertility.